2022
DOI: 10.1007/s00253-022-12071-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of proteins from the 3N5M family reveals an operationally stable amine transaminase

Abstract: Amine transaminases (ATA) convert ketones into optically active amines and are used to prepare active pharmaceutical ingredients and building blocks. Novel ATA can be identified in protein databases due to the extensive knowledge of sequence-function relationships. However, predicting thermo- and operational stability from the amino acid sequence is a persisting challenge and a vital step towards identifying efficient ATA biocatalysts for industrial applications. In this study, we performed a database mining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…ATA-Vfl is a dimeric, (S)selective wildtype transaminase from Vibrio fluvialis, and it has been frequently examined and used in several studies [60][61][62][63][64]. ATA-Bmu is an (S)-selective wildtype transaminase from Burkholderia multivorans, and was recently discovered by database mining as a member of the β-alanine:pyruvate transaminase family [65]. Enzymes of this family exhibit a tetrameric structure associated with high operational stability.…”
Section: Introductionmentioning
confidence: 99%
“…ATA-Vfl is a dimeric, (S)selective wildtype transaminase from Vibrio fluvialis, and it has been frequently examined and used in several studies [60][61][62][63][64]. ATA-Bmu is an (S)-selective wildtype transaminase from Burkholderia multivorans, and was recently discovered by database mining as a member of the β-alanine:pyruvate transaminase family [65]. Enzymes of this family exhibit a tetrameric structure associated with high operational stability.…”
Section: Introductionmentioning
confidence: 99%
“…The operating stabilities of the ATAs from this study are better than those reported for Vibrio fluvialis ATA [27]. They are in the same range as a wild-type ATA identified in a metagenomic library probably originating from Pseudomonas sp., TA-5LH9 [28], but less stable than the engineered variant of TA-5LH9 created by Bo ¨rner and co-workers [29] and our recently characterized wild-type ATA from Bulkholderia multivorans [30], which both are tetrameric enzymes.…”
Section: Stabilitiesmentioning
confidence: 82%
“…The optimal reaction temperature for the enzyme was determined to be 55 °C, as shown in Figure 3B. Ideally, enzymes should exhibit high thermostability under “operational stability” (when substrates and conditions required for catalysis are present), similar to the higher thermal stability they should possess under storage conditions (referred to as “resting stability” because the catalyst is in a more stable resting state) [27] . To assess the thermal stability of M16AT under operational conditions, its stability under storage conditions was first tested.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, enzymes should exhibit high thermostability under "operational stability" (when substrates and conditions required for catalysis are present), similar to the higher thermal stability they should possess under storage conditions (referred to as "resting stability" because the catalyst is in a more stable resting state). [27] To assess the thermal stability of M16AT under operational conditions, its stability under storage conditions was first tested. Figure 3C shows that after treatment at 55 °C for 30 minutes under storage conditions, the residual activity of M16AT was approximately 45 %.…”
Section: Identification Of Enzymatic Propertiesmentioning
confidence: 99%